Potency of Bioactive Compound of Cassava Leaf Paste to Support Physiological Performance of Quail - Jumadin, La; Maheshwari, Hera; Ulupi, Niken; Satyaningtijas, Aryani Sismin (Jurnal Ilmu dan Teknologi Peternakan Tropis, 2022)
Cassava leaf paste is an alternative substance in supporting the physiological performance of quail. Cassava leaf paste contains nutritional compositions such as water, ash, crude protein, crude fiber, fat, and carbohydrate. Cassava leaf paste has high crude protein and low crude fiber. The content of β-carotene and chlorophyll in cassava leaf paste has the ability as an antioxidant. Cassava leaf paste also contains phytochemicals such as flavonoids, saponins, tannins, sitosterol, and stigmasterol. The concentration of phytochemical has slightly higher flavonoid content, moderate tannins and saponins, and high sitosterol and stigmasterol. These phytochemicals act as antioxidants, antimicrobials, anti-inflammatory, improve the immunomodulatory system and reduce cholesterol. In addition, cassava leaf paste contains macro minerals such as P and Ca, as well as microminerals (Fe, Cu, Mn, and Zn). These minerals act as an antioxidant increases nutrient absorption, enhances immune response, and take part in mineralization during eggshell formation. Cassava leaf paste also has low levels of cyanide. Based on the nutritional content, phytochemicals, macro and micro minerals, and cyanide acid, cassava leaf paste has the potential to increase the physiological performance of quail.